Xanthophyllomyces dendrorhous (Phaffia rhodozyma) on stromata of Cyttaria hariotii in northwestern Patagonian Nothofagus forests - Libkind Frati, Diego (2011)
The occurrence and distribution of Xanthophyllomyces dendrorhous associated with Cyttaria hariotii parasitizing three Nothofagus species (N. dombeyi, N. antarctica and N. pumilio) in northwestern Patagonia (Argentina), as well as the factors that may affect this distribution were herein studied. Between 2000 and 2007, samples were obtained from 18 different locations. Based on physiological tests and morphological characteristics of sexual structures, 72 isolates were identified as X. dendrorhous. Representative strains were studied by MSP-PCR fingerprinting and sequence analysis of the ITS region. MSP-PCR fingerprints were similar for the newly isolated strains, and were also identical to the profiles of the strains previously found in this region. Patagonian strains appear to be a genetically uniform and distinct population, supporting the hypothesis that the association with different host species has determined genetically distinct X. dendrorhous populations worldwide. X. dendrorhous was recovered from N. dombeyi and N. antarctica. Approximately half the sampling sites and samples were positive for X. dendrorhous, but the isolation recovery rate was low. X. dendrorhous was absent in the early stages of ascostromata maturation, becoming more abundant in later stages. The present work represents a step forward in the understanding of the natural distribution and ecology of this biotechnologically relevant yeast.